1986
DOI: 10.1099/00222615-21-3-189
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Streptococcus sanguis and S. mitior by whole-cell rhamnose content and possession of arginine dihydrolase

Abstract: Summary. Whole-cell rhamnose concentrations were measured in 48 strains of streptococci resembling Streptococcus sanguis and S. mitior. Physiological characteristics were tested by the API-20/Strep system, and it was found that "typical" S. sanguis (arginine positive, aesculin positive) contained significant amounts of rhamnose, while "typical" S. mitior (arginine negative, aesculin negative) contained very low or undetectable amounts of rhamnose. Both groups contained dextran-positive and dextran-negative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Dextran-negative erythromycin-resistant strains of S. sanguis have also been described recently (Harrison et al,198%). This is surprising because although dextran-negative S. sanguis have been reported, they are relatively uncommon and most strains characteristically synthesise polysaccharides (Price et al, 1986). In our previous study, bacteria were isolated that could grow on agar supplemented with amoxycillin 40 mg/L and, as this concentration corresponds to the peak serum levels of the antibiotic, they were considered to pose a potentially significant threat to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dextran-negative erythromycin-resistant strains of S. sanguis have also been described recently (Harrison et al,198%). This is surprising because although dextran-negative S. sanguis have been reported, they are relatively uncommon and most strains characteristically synthesise polysaccharides (Price et al, 1986). In our previous study, bacteria were isolated that could grow on agar supplemented with amoxycillin 40 mg/L and, as this concentration corresponds to the peak serum levels of the antibiotic, they were considered to pose a potentially significant threat to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Although dextran-negative S . sanguis strains have been described (Price et al, 1986), most studies report that an overwhelming majority of strains produce extracellular polysaccharides from sucrose. Some of the highly amoxycillin-resistant streptococci from our recent study (Woodman et al, 1985) have now been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The atypical S . mitior-like strain STH 135(J), arginine-negative but containing large amounts of rhamnose (Price et al, 1986), was classified intuitively as S . mitior on the basis of physiological reactions but grouped with S .…”
Section: U3mentioning
confidence: 99%
“…Many species of oral bacteria, some of which are dom inant plaque microorganisms, utilize arginine by hydroly sis yielding ammonia [Hardie and Bowden, 1976;Price et al, 1986;Krai and Daneo-Moore, 1981;Coykendall, 1989].…”
mentioning
confidence: 99%